Implementasi Kebijakan Peraturan Daerah Tanjungpinang Nomor 7 Tahun 2018 Tentang Ketertiban Umum: (Studi Kasus Pada Pedagang Kaki Lima Di Taman Tepi Laut) - Putri Febriyanti; Oges Susfita Putri; Mellyana Candra (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
An important step to improve urban planning and provide comfortable public space for the community. Street vendors often disturb the order and beauty of the environment, in the implementation of this policy the Tanjungpinang city government needs to involve various related parties, such as the Trade Office, Cleaning Office, Transportation Office. The first step that must be done is to socialize to traders about their relocation to a place that has been provided by the government. The implementation of this policy can be expected to create a more orderly and comfortable atmosphere for the community.